Acharya - Temples of India Project Team (Jio Institute, 2024)
The adhisthana has depictions of various Hindu gods and goddesses framed within elaborately carved panels. This panel depicts a male figure seated in the udichya mudra (cross-legged position). The panel depicts a central male figure seated on a raised asana in the udichya mudra (cross-legged position). At the bottom of his asana, a pair of footwear is placed. Two female attendants are present on either side, standing in front of trees in the background. The faces, feet, and hands of the figures are broken and their attributes are not clear.